(untitled) (Simbiótica. Revista Eletrônica, 2020)
The purpose of the article is to think about one of the most important issues regarding the pandemic: the complexity of the disputes over its governance. For this, we approached a set of texts written in the heat of the moment, by philosophers and sociologists who faced the challenge of thinking, in a situation of full uncertainty and unpredictability, the social, political, cultural and even epistemic consequences of the pandemic. For this, we divided the article into three parts that interpenetrate: science as moral regulation, the problems of biopolitics and Globalization and informatization of society. Keywords: Pandemic; science; biopolitics; informatization.